Next generation dark-field microscopy: from high-speed single particle tracking to label-free imaging - Meng, X (2019)
This thesis details the improvement and implementation of a total internal reflection dark-field scattering microscope, in terms of pushing the boundaries of its sensitivity and spatiotemporal resolution, to study the bending flexibility of DNA on biologically important length scales. Furthermore, by observing the scattering intensity response to the reconfiguration of the electric double layer on a substrate, dark-field microscopy has been brought into the field of label-free imaging, establishing a novel contrast mechanism. Specifically, Chapter 2 describes the basics of light scattering and tethered particle motion and elaborates various designs to apply total internal reflection-based dark-field microscopy. After characterisation and quantitative comparison regarding their signal-to-noise ratio and background noise suppression performance, high- speed tracking of 20 nm diameter gold nanoparticles with few nanometre localisation precision and few microsecond exposure time is demonstrated with the optimised set-up. Chapter 3 combines this imaging capability with tethered particle motion to directly address the mechanical properties of double-stranded DNA shorter than 160 base pairs without significant volume exclusion effect. Chapter 4 takes the advantage of the short DNA tether functionalised with a charged gold nanoparticle which behaves like a nanospring in the presence of an alternating electric field, to measure the electrophoretic force and charge with femtonewton sensitivity. In the last chapter, total internal reflection-based dark-field microscopy is applied to optically image the electric double layer around nanostructures on an ITO substrate based on the potentiodynamic optical contrast mechanism and thus proves its potential, at least in principle, for label-free imaging at the single molecule level.